A phenomenological argument against instrumentalism. (7th October 2021) - DaVia, Carlo
Abstract: Instrumentalism as a theory of practical reasoning has been both widely held and difficult to dethrone. The theory holds that good practical reasoning need only involve determining suitable means to pre‐determined ends. The theory is difficult to dethrone because critiques of it tend to specify aspects of reasoning that either do not seem practical, strictly speaking, or can be re‐described as a series of episodes of means‐end reasoning. Either way, instrumentalism dodges these criticisms raised against it. This paper presents a phenomenological argument that cannot be so dodged. The argument is this: practical reasoning is not merely instrumental because our considering an exemplary means to some end sometimes modifies our concept of that end within one and the same episode of practical deliberation. Such modification is possible because in any exercise of reason in which we apply a concept to a particular, the exemplarity of the particular can imbue our concept with new meaning. If exemplary means can modify our practical ends in this way, then instrumentalism is false.